Claymation / Nur Fatihah Muhammad Nazim ... [et al.] - Muhammad Nazim, Nur Fatihah; Ibrahim, Noor Arifah; Zainal Abidin, Noranisa; Wan Mohd, Wan Norhakimah; Mohamad Fauzi, Muhammad Izzat Najmi (2023)
Claymation’s main goal of producing this product is to provide an initiative for our target market mainly parents and those who works in the educational sectors such as nursery or could be an art teacher to choose a better option of safe and non-hazardous modelling clay that is suitable for toddlers or children to play with. To cater with the health and safety issues regarding the use of chemical and artificial colours in the existing modelling clays that potentially harmful to its consumers, Claymation come out with any improvement with the formulation of utilising only safe and organic ingredients that would not impart any harm as we only extract colours from plants and fruits such as blue peas flowers, tomatoes, mangoes and screwpine leaves for blue, red, yellow and green colours respectively.